MALADMINISTRATION AND INTENTIONALITY ON THE CRIMINAL CORRUPTION COURT IN INDONESIA - Elstonsius Banjo; Surastini Fitriasih; Eva Achjany Zulfa (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2022)
Maladministration and state financial losses have been the basis of the Criminal Court of Corruption’s decision to punish the defendant. Judges' decisions are often based on proven objective facts while subjective facts, including the "intentions" of offenders, are often disregarded even though the principle of criminal responsibility presupposes both objective and subjective aspects as a basis sentencing defendants. As a result, the enforcement of corruption in Indonesia has become a long-standing and polemic issue of justice. This study examines how "intention" is the main element used to determine whether the defendant is guilty under Article 2 and Article 3 of the "PTPK Law" in the Indonesian Corruption Court. The analysis is based on the theory of Criminal Responsibility through the "analytical and critical approach" in which its aim is to avoid "liability without fault" and to ensure that "committed intentionally" is the main element used in decision making regarding corruptor sentencing. Abstrak: Maladministrasi dan perhitungan riil kerugian keuangan negara telah menjadi dasar Pengadilan Tindak Pidana Korupsi untuk memidana terdakwa sesuai Pasal 2 dan Pasal 3 UU PTPK. Keputusan hakim lebih membuktikan/mempertimbangkan fakta objektif daripada fakta subjektif atau "niat jahat" pelaku atas perbuatan yang dilakukan. Padahal asas pertanggungjawaban pidana mensyaratkan unsur objektif dan subjektif sebagai dasar pengadilan untuk menjatuhkan pidana terhadap terdakwa. Akibatnya, penegakan hukum kasus korupsi di Indonesia menjadi polemik keadilan yang berkepanjangan, terutama terhadap seseorang yang telah dipidana bersalah. Penelitian ini mengkaji bagaimana “niat jahat" pelaku menjadi unsur utama untuk menyatakan kesalahan atas tindak pidana korupsi pada Pasal 2 dan Pasal 3 “UU PTPK” di Pengadilan Tindak Pidana Korupsi di Indonesia. Analisis didasarkan pada asas dan teori Kesalahan melalui “pendekatan analitis-kritis”. Tujuannya untuk menghindari “pertanggunjawaban pidana tanpa kesalahan”, dan “melakukan dengan sengaja” adalah unsur utama untuk menyatakan kesalahan dan memidana pelaku.Kata Kunci: Maladministrasi, Kesengajaan, Pengadilan Korupsi, Keadilan